2020
DOI: 10.1002/adom.202000168
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Broadband Photodetectors of Heterogeneous 2D Inorganic Molecular Sb2O3/Monolayer MoS2 Crystals Grown via Chemical Vapor Deposition

Abstract: The newly emerged 2D materials heterostructures, including layered and nonlayered structures, are regarded as the building blocks for future high performance optoelectronic devices. However, it still remains a great challenge to directly synthesize 2D heterostructures for realizing broadband detection in photodetectors. In this work, the growth of vertically stacked inorganic molecular Sb2O3/monolayer MoS2 heterostructures through a two‐step chemical vapor deposition method is demonstrated, and high performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Singh et al 371 reported Pd/Al 2 O 3 /MoS 2 /ITO photodetector showing photoresponsivity of 488 A W À1 , detectivity of 8.22 Â 10 12 Jones and EQE of 1.9 Â 10 5 % at 308 nm wavelength under laser light intensity of 13.6 mW/cm 2 with 1 V applied bias voltage. Ye et al 372 demonstrated vertical growth of Sb 2 O 3 akes on monolayer MoS 2 crystals by using CVD technique. The Sb 2 O 3 akes of different thickness and size covered monolayer MoS 2 crystals in 10, 21, 44, 54 and 100% ratio and their based backgated FETs fabricated on SiO 2 /Si wafer affected the carrier mobility and subthreshold swing (SS) of the Sb 2 O 3 /MoS 2 hybrid photodetectors.…”
Section: Mos 2 /Inorganic Semiconductor Heterostructuresmentioning
confidence: 99%
“…Singh et al 371 reported Pd/Al 2 O 3 /MoS 2 /ITO photodetector showing photoresponsivity of 488 A W À1 , detectivity of 8.22 Â 10 12 Jones and EQE of 1.9 Â 10 5 % at 308 nm wavelength under laser light intensity of 13.6 mW/cm 2 with 1 V applied bias voltage. Ye et al 372 demonstrated vertical growth of Sb 2 O 3 akes on monolayer MoS 2 crystals by using CVD technique. The Sb 2 O 3 akes of different thickness and size covered monolayer MoS 2 crystals in 10, 21, 44, 54 and 100% ratio and their based backgated FETs fabricated on SiO 2 /Si wafer affected the carrier mobility and subthreshold swing (SS) of the Sb 2 O 3 /MoS 2 hybrid photodetectors.…”
Section: Mos 2 /Inorganic Semiconductor Heterostructuresmentioning
confidence: 99%
“…However, an inverse movement occurs at a lower temperature ( T = 80 K); namely, the holes accumulate in a colloidal PbS quantum dot (QD) while electrons transfer to the graphene channel . This temperature-drive carrier transfer process increases the trapping time, which is beneficial for higher photoresponsivity and photoconductive gain. , …”
Section: Physical Sensorsmentioning
confidence: 99%
“…294 This temperature-drive carrier transfer process increases the trapping time, which is beneficial for higher photoresponsivity and photoconductive gain. 162,295 (2) Photogating Effect. The photogating effect is a way of light-induced modification in carrier density and channel conductance, which is ascribed to the additional gate voltage caused by trap charges at the interface.…”
Section: Optical Sensorsmentioning
confidence: 99%
“…The WS 2 has the smallest piezoelectric effect, and moving downward in group 6 (transition metals) or group 16 (chalcogenides) enhances the magnitude of the effect until MoTe 2 , with the largest coefficient, is reached. The 2D materials can withstand huge strains with high crystallinity, which are the research hotspots of high-performance piezoelectric materials [51][52][53]. Wu et al first proposed the piezoelectric performance of a single-layer MoS 2 -based device coupled with an external load resistor (figure 3(d)-(i)) [54].…”
Section: Unique 2d Materials For Tribotronic Fetsmentioning
confidence: 99%